(untitled) (Global Journal of Science Frontier Research, 2012)
The levels of fatty acids, phospholipids and zoosterols were determined in the edible parts of three land snails consumed in Nigeria [Archachatina marginata, Archatina (archatina) archatina and Limicolaria sp.)] on dry weight basis. Results showed crude fat varied from 2.22-2.38 g/100 g; SFA varied from 37.5-49.8 % of total fatty acids, total unsaturated fatty acids varied from 50.2-62.5 %, PUFA ranged from 25.5-38.7 %. In the phospholipids, phophatidylcholine was highest in all the samples with a range of 1.55-2.88 mg/100 g. Only cholesterol had results > 0.00 mg/100 g in the sterols with a value range of 37.1 -45.1 mg/100 g. Eicosadienoic acid (C20: 2 cis -11, 14) was the highest PUFA in all the samples with range values of 8.36-16.7 mg/100 g.